LPG equipment and accessories. Static welded steel cylindrical pressure vessels, serially produced for the storage of Liquefied Petroleum Gas (LPG) having a volume not greater than 13 m³. Design and manufacture. (24th August 2020) - British Standards Institution,
No abstract available